Numerical Modeling of Soil Erosion with Three Wall Laws at the Soil-Water Interface - El Assad, Hatim; Kissi, Benaissa; Hassan, Rhanim; Angel, Parron Vera Miguel; Dolores, Rubio Cintas Maria; Chafik, Guemimi; Kacem-Boureau, Mariem (Civil Engineering Journal, 2021)
In the area of civil engineering and especially hydraulic structures, we find multiple anomalies that weakens mechanical characteristics of dikes, one of the most common anomalies is erosion phenomenon specifically pipe flow erosion which causes major damage to dam structures. This phenomenon is caused by a hole which is the result of the high pressure of water that facilitate the soil migration between the two sides of the dam. It becomes only a question of time until the diameter of the hole expands and causes destruction of the dam structure. This problem pushed physicist to perform many tests to quantify erosion kinetics, one of the most used tests to have logical and trusted results is the HET (hole erosion test). Meanwhile there is not much research regarding the models that govern these types of tests. Objectives: In this paper we modeled the HET using modeling software based on the Navier Stokes equations, this model tackles also the singularity of the interface structure/water using wall laws for a flow turbulence. Methods/Analysis: The studied soil in this paper is a clay soil, clay soil has the property of containing water more than most other soils. Three wall laws were applied on the soil / water interface to calculate the erosion rate in order to avoid the rupture of such a structure. The modlisitation was made on the ANSYS software. Findings: In this work, two-dimensional modeling was carried of the soil.in contrast of the early models which is one-dimensional model, the first one had shown that the wall-shear stress which is not uniform along the whole wall. Then using the linear erosion law to predict the non-uniform erosion along the whole length. The previous study found that the wall laws have a significant impact on the wall-shear stress, which affects the erosion interface in the fluid/soil, particularly at the hole's extremes. Our experiment revealed that the degraded profile is not uniform.Â Doi: 10.28991/cej-2021-03091742 Full Text: PDF